2013
DOI: 10.1128/jb.00353-13
|View full text |Cite
|
Sign up to set email alerts
|

The Function of the Na + -Driven Flagellum of Vibrio cholerae Is Determined by Osmolality and pH

Abstract: bVibrio cholerae is motile by its polar flagellum, which is driven by a Na ؉ -conducting motor. The stators of the motor, composed of four PomA and two PomB subunits, provide access for Na ؉ to the torque-generating unit of the motor. To characterize the Na ؉ pathway formed by the PomAB complex, we studied the influence of chloride salts (chaotropic, Na ؉ , and K ؉ ) and pH on the motility of V. cholerae. Motility decreased at elevated pH but increased if a chaotropic chloride salt was added, which rules out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 47 publications
(49 reference statements)
1
25
1
Order By: Relevance
“…The endogenous Na + content of the medium was 11 mM as determined by atomic absorption spectroscopy [17]. If indicated, D,L-lactate (33 mM final concentration) was added from a stock solution adjusted to pH 6.5 with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…The endogenous Na + content of the medium was 11 mM as determined by atomic absorption spectroscopy [17]. If indicated, D,L-lactate (33 mM final concentration) was added from a stock solution adjusted to pH 6.5 with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…V. cholerae O395, devoid of the qseC-like gene, exhibited reduced motility on serum-SAPI compared to the reference strain, but motility was still enhanced by E or NE, suggesting the presence of additional systems for catecholate sensing, like QseE, BasS, or CpxA (37). Expression levels of the pomB gene coding for a structural component of the flagellar stator complex (38) and the qseC-like gene were increased when V. cholerae was exposed to E or NE. This indicates an NE-or E-triggered signal transduction chain in V. cholerae, which might be related to the QseC-dependent signaling cascades described for S. enterica (4) and E. coli (29,39).…”
Section: Discussionmentioning
confidence: 99%
“…was also affected by the presence of NaCl ( Figure 4 ) and, perhaps, specifically by chloride ions (data not shown). Halang et al (2013) reported that in V. cholerae chloride ions act as chaotropic agents and enhance cell motility. For instance, the nano-machine flagellum is composed of several subunits, MotA and MotB in H + -dependent, or PomA and PomB in Na + -dependent flagella (Halang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Halang et al (2013) reported that in V. cholerae chloride ions act as chaotropic agents and enhance cell motility. For instance, the nano-machine flagellum is composed of several subunits, MotA and MotB in H + -dependent, or PomA and PomB in Na + -dependent flagella (Halang et al, 2013). Chloride ions disrupt hydrogen bonds between water molecules that interact with PomB protein, specifically with D23 and S26 residues.…”
Section: Discussionmentioning
confidence: 99%